Guidance Counseling with a Spiritual Approach in Improving Adolescent Mental Health - Mulyani, Puput Sri (Archives of The Medicine and Case Reports, 2024)
Adolescence is a transition period from childhood to adulthood, so they are vulnerable to experiencing various mental health problems. Guidance counseling with a spiritual approach is one effort to improve adolescent mental health. This research aims to determine the effect of counseling guidance with a spiritual approach on adolescent mental health. This research uses a quasi-experimental method with a control group design. The research sample consisted of 60 teenagers, who were divided into two groups, namely the experimental group who received counseling guidance with a spiritual approach and the control group who did not receive counseling guidance. Data was collected using a mental health questionnaire. The research results show that counseling guidance with a spiritual approach has a positive effect on teenagers' mental health. Adolescents who receive counseling guidance with a spiritual approach have higher mental health scores compared to adolescents who do not receive counseling guidance.